Middle leadership roles in universities: Holy Grail or poisoned chalice. Issue 3 (4th May 2018) - Thornton, Kate; Walton, Jo; Wilson, Marc; Jones, Liz
ABSTRACT: Middle leadership roles in higher education have been identified as important for institutional effectiveness yet fraught with tensions, and those in middle leadership roles often feel unprepared and unsupported. This study of the responsibilities, skills and competencies, and support required for heads of school in a New Zealand university, drew on a survey and interviews with heads and focus groups or interviews with a range of stakeholders. The research found that while heads found satisfaction in their role, they also faced challenges associated with people management, workload and impact on their research careers. There was widespread agreement among stakeholders about the capabilities needed for the role and an awareness of the barriers to effectiveness. Suggestions for making the role more appealing include reducing workload, providing learning and development programs, clarifying the balance of professional and personal competencies required, and encouraging the distribution of leadership.